Loss of Dfg5 glycosylphosphatidylinositol‐anchored membrane protein confers enhanced heat tolerance in Saccharomyces cerevisiae. (7th January 2015) - Nasution, Olviyani; Lee, Jaok; Srinivasa, Kavitha; Choi, In‐Geol; Lee, Young Mi; Kim, Eunjung; Choi, Wonja; Kim, Wankee
Summary The protein product of Saccharomyces cerevisiae DFG5 gene is a glycosylphosphatidylinositol (GPI)‐anchored plasma membrane protein and a putative glycosidase/glycosyltransferase that links other GPI‐anchored proteins to β‐glucans in the cell wall. Upon exposure to heat (41°C), DFG5 deletion mutant dfg5Δ displayed significantly enhanced heat tolerance as well as lowered level of reactive oxygen species and decreased membrane permeability compared with those in the control (BY4741). Comparative transcriptome profiles of BY4741 and dfg5Δ revealed that 38 and 23 genes were up‐ and down‐regulated in dfg5Δ respectively. Of the 23 down‐regulated genes, 11 of 13 viable deletion mutants were identified to be tolerant to heat, suggesting that the down‐regulation of those genes might have contributed to the enhanced heat tolerance in dfg5Δ. Deletion of DFG5 caused slight activation of mitogen‐activated protein kinases Hog1 in the high‐osmolarity glycerol pathway and Slt2 in the cell wall integrity pathway. Therefore, a model is proposed on the signal transduction pathways associated with deletion of DFG5 upon heat stress.